1987
DOI: 10.1088/0029-5515/27/8/005
|View full text |Cite
|
Sign up to set email alerts
|

Incremental energy confinement time during H0beam heating in JT-60

Abstract: Characteristics are presented of the energy confinement time resulting from neutral hydrogen beam heating of JT-60 tokamak plasmas with a plasma current, Ip, of 1-2 MA, a line averaged electron density, n e , of 1.5-7 X 10 19 m~3 and an absorbed beam power, P a b S , up to 20 MW. The plasma energy content follows an offset linear relation to the absorbed power. The incremental energy confinement time for thermal components, rg c , is almost independent of I p and n e at 60 ms, while the incremental energy conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1988
1988
1990
1990

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…1. The energy confinement properties of the discharges follow the saturated Ohmic confinement scaling (the energy confinement time is typically up to 450 ms) and the L-mode scaling during neutral beam heating [11]. The Ohmic data are taken near the end of the flat-top of the plasma current where the discharges are nearly stationary.…”
Section: Experimental Conditions and Characteristic Resultsmentioning
confidence: 99%
“…1. The energy confinement properties of the discharges follow the saturated Ohmic confinement scaling (the energy confinement time is typically up to 450 ms) and the L-mode scaling during neutral beam heating [11]. The Ohmic data are taken near the end of the flat-top of the plasma current where the discharges are nearly stationary.…”
Section: Experimental Conditions and Characteristic Resultsmentioning
confidence: 99%
“…A comparison of the power flow of the three different heating systems in shot E7928 is given in Table I, where Pft, • P ^ + P& s + P 0H > Padd • PLH + P N b B s + AP 0H and AW* = W**, -W 0H -AW 6lTc (AW finc is the change in stored energy due to the density increase deduced from the OH scaling [23]). Since the incremental energy confinement time of the bulk plasma in the combined NB + LH heating case is considered to be the normal value (~53 ms), as mentioned before, it is possible to estimate the stored energy of the tail (Table I).…”
Section: Table I Comparison Of the Heating Efficiency In Shot E7928mentioning
confidence: 99%
“…The incremental thermal diffusivity is independent of the average density; this is clear from our previous study [7] where the energy loss has been shown to be dominated by the conduction loss, and the incremental energy confinement time for the thermal component is…”
Section: Transport Modelling Based On the Heat Pinchmentioning
confidence: 63%
“…As shown in Ref. [7], the plasma stored energy during Ohmic heating increases with the average plasma density. The incremental energy confinement time for the thermal component is independent of (or weakly dependent on) the plasma density and the plasma current; however, no full current scan was made.…”
Section: Transport Modelling Based On the Heat Pinchmentioning
confidence: 64%
See 1 more Smart Citation